Strengthening Religious Moderation in Madrasahs: An In-Depth Evaluation - Sudarman, Sudarman; Sahraini, Sahraini; Kartini, Kartini (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
This study evaluates the implementation and outcomes of religious moderation education in three madrasahs—MIS Bokin, MIS Rantepao, and MTs Rantepao—located in North Toraja Regency. Employing the CIPP (Context, Input, Process, Product) evaluation model and a qualitative approach, the research explores how religious moderation principles are integrated into Islamic Religious Education (PAI) lessons and extracurricular activities. Data were gathered through observations, interviews, and document analysis, involving principals, teachers, and students as key informants. The findings indicate that religious moderation education is embedded effectively into both curricular and extracurricular activities. Through PAI lessons, teachers integrate values such as tolerance, harmony, and critical thinking using innovative methods like Active Debate and Everyone Is a Teacher Here. These approaches enable students to internalize moderation values naturally. Extracurricular activities, such as interfaith collaborations during religious holidays, provide practical applications of these principles, fostering mutual respect and inclusivity among students. The outcomes reveal enhanced national commitment, tolerance, and critical thinking skills among students. The programs address contemporary challenges, such as the spread of radical ideologies, by creating a positive and inclusive school environment. A systematic implementation process, supported by continuous evaluation, ensures the programs’ effectiveness and adaptability to the needs of students. This study concludes that religious moderation education at these madrasahs serves as an exemplary model for fostering harmony and coexistence in diverse educational contexts. Recommendations include consistent program evaluation, leveraging technology for broader outreach, and expanding these practices to other educational institutions.